Peran HbA1c dalam progresi dan prognosis COVID-19 pada pasien diabetes mellitus - Ni Luh Parameswari Praptika; Kadek Wisnu Segara Karya (Intisari Sains Medis, 2021)
Objective: This systematic review determined the role of HbA1c in the progression and prognosis of COVID-19 in patients with diabetes mellitus from several previously published articles.Method: We searched from an open-access database according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines and the PICO criteria. The inclusion criteria for the article search included: 1) COVID-19 patients with diabetes mellitus; 2) full articles; 3) English articles; 4) article publication time range from 2016 to 2021. Quality assessment for each article is evaluated using a checklist from Strengthening the Reporting of Observational Studies in Epidemiology (STROBE).Result: We obtained two cohort studies and four cross-sectional studies of all the articles reviewed from 2019-2021. All studies evaluated the role of HbA1c in the progression, prognosis, and mortality of COVID-19 patients with diabetes mellitus. Most of the reported studies showed an association between elevated HbA1c and worsening of the COVID-19 disease prognosis. The association was assessed by the patient's clinical deterioration included lower oxygen saturation, increased NLR (neutrophil-lymphocyte ratio), the tendency to lymphopenia, improved renal function, increased ICU admission, and mechanical ventilation and increased ventilation mortality.Conclusion: A high HbA1c was closely related to a worse COVID-19 prognosis in clinical development and mortality. We found the potential for developing a scoring system to predict the worsening and mortality of COVID-19 and improve the quality of prevention and management of COVID-19, especially in patients with diabetes mellitus. Tujuan: mengkaji peran HbA1c dalam progresi dan prognosis COVID-19 pada pasien diabetes mellitus dari beberapa literatur yang telah dipublikasi sebelumnya.Metode: Pencarian literatur secara sistematis dilakukan pada basis data dengan akses terbuka sesuai dengan pedoman PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) dan kriteria PICO. Kriteria inklusi pencarian artikel antara lain: 1) pasien COVID-19 dengan diabetes mellitus; 2) artikel lengkap; 3) artikel berbahasa Inggris; 4) rentang waktu terbit artikel dari tahun 2016 hingga tahun 2021. Penilaian kualitas pada setiap artikel yang dievaluasi menggunakan checklist dari Strengthening the Reporting of Observational Studies in Epidemiology (STROBE).Hasil: Dari seluruh artikel yang dikaji dari tahun 2019-2021, didapatkan 2 studi kohort dan 4 studi potong lintang. Keseluruhan studi mengevaluasi peran HbA1c dalam progresi, prognosis, maupun mortalitas pada pasien COVID-19 dengan diabetes mellitus. Sebagian besar penelitian yang dilaporkan menunjukkan keterkaitan antara peningkatan HbA1c dan perburukan prognosis penyakit COVID-19 yang dinilai dari perburukan klinis pasien yaitu saturasi oksigen yang lebih rendah, meningkatnya NLR (neutrophil lymphocyte ratio), kecenderungan limfopenia, fungsi ginjal yang meningkat, peningkatan admisi ICU dan pemanfaatan ventilator mekanik serta meningkatnya mortalitas.Simpulan: HbA1c yang tinggi terbukti berhubungan erat dengan prognosis COVID-19 yang lebih buruk ditinjau dari perkembangan klinis hingga tingkat mortalitas yang terjadi. Hal ini menunjukkan potensi berkembangnya sistem skoring untuk memprediksi perburukan dan mortalitas COVID-19 serta peningkatan kualitas pencegahan dan tatalaksana COVID-19 terutama pada pasien diabetes mellitus.